Antarctic Krill and the Temporalities of Oceanic Abundance, 1930s-1960s - Alessandro Antonello (2022)
In the decades after World War II, oceans were envisioned as sites of resource abundance that would underpin global development. This essay investigates Antarctic krill and its potential “surplus” as one articulation of this abundance, attending to the cultural and epistemic strategies at play in constituting this ocean abundance. Concentrating on the work of Neil Mackintosh, a world-leading British whale biologist working within governmental scientific bodies, this essay identifies temporal imaginings and sensibilities as being central to his claims around krill abundance and its seeming surplus in the context of whale stocks significantly diminished through overexploitation. Mackintosh’s temporalities of abundance were generated in three overlapping and mutually reinforcing sites: the archive of the colonial scientific survey he worked for, the decades of his career, and the recovery of polar seal populations. The story of the krill surplus and the temporalities underpinning it allows for a more complex reckoning with ideas of scarcity and abundance as well as further demonstrating the need to see the temporalities at work in constituting environments and the scientific labor in them.